Constitutional identity in the argumentation of decisions of constitutional courts - Shcherbanyuk, Oksana (Constitutional and legal academic studies, 2020)
The latest trend in modern European constitutionalism is the issue of constitutional identity. Constitutional courts, which are the embodiment not only of the protection of the Constitution, but also of the limitation of power, are influential subjects of assessing the country’s international obligations and their implementation in national legislation. The purpose of the article is to analyze the constitutional identity in the argumentation of decisions of constitutional courts. The research method is a comparative legal analysis of the practice of constitutional review bodies in order to assess the expression of the concept of respect for national identity, which has become a condition and principle of legal integration in the European region. In addition, empirical analysis of decisions of constitutional courts was used. Using the system-structural method, the doctrine of «constitutional boundaries» as a component of constitutional identity is analyzed. It is justified that the concept of «identity» appeared and began to be actively used by European constitutional courts to justify decisions related to the processes of European integration and the expansion of the influence of supranational institutions of international organizations, including the European Union. It is proved that the decisions of constitutional courts should be based on national legal values, taking into account international practice and the principle of the supremacy of the Constitution. At the same time, national courts must take into account the country’s international obligations when making decisions. In today’s world, constitutional courts cooperate with the courts of international organizations, which form a common case law in the member states, in particular on the interpretation of human rights. This is manifested in the citation by constitutional courts in their acts of decisions of supranational judicial bodies. It should also be noted that the constitutional court may be guided by the positions of international courts in forming its legal position, but according to the doctrine of judicial discretion, the national court is free to assess the circumstances of the case and it is best acquainted with national features and specifics of national law.
Keywords: constitutional proceedings; constitutional argumentation; national identity; interpretive argument; constitutionalism